Knowledge of the Ethical Implications on Public of the Health Measures taken by Decision-Makers at the Uruguayan Ministry of Health (Revista Iberoamericana de Bioética, 2018)
This paper endeavors to provide an explanation of health and the make-up of healthcare through distributive justice theories and access to the development of capabilities as the basis of a just healthcare structure. It also looks at matters around first level attention in healthcare as fundamental in the development of capabilities and access to functional diversity. It amounts, therefore, to a redefinition of bioethical contractualism, applied at the structure as basis of justice and the capability development.
Keywords: bioethics; public health ethics; decision-making